FORENSIK TEKNOLOGI INFORMASI PADA HOTSPORT AREA (Study Kasus pada HotSport Fatek Area) - ., Haryono; Trias H, Rahmadya (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2010)
Privacy and ease of information technology tend to make people depend on availability. Computer network system is attached day after day without compromise. These attacks are designed to steal personal identity, to disable the online presence of business, or to completely destroy sensitive information that is essential for personal or business goals. All of this is the responsibility of each organization to establish system that is safe enough to protect their own interests as well as those whosubscribe. Computer crime continues to, so does the need for professional computer personnel who are trained in dealing with computer crime forensics to gather digital evidence, in terms of applying the tools necessary security, and cooperate with law enforcement agencies. This research paper presents the design and implementation of an experiment and Computer Security Forensic Analysis (CSFA) laboratory and tools associated with it. Laboratory is expected to be a trainingfacility for computer security in the future